The effect of appraisal interviews and target agreements on employee effort - New evidence using representative data - Patrick Kampkötter; Patrick Maier (University of Tübingen, Faculty of Economics and Social Sciences, 2020)
Performance measurement and evaluation systems are among the most common management instruments. An integral element of this process is the use of targets, typically set in appraisal interviews and formalized via written target agreements. In this paper, we investigate the relationship between performance management and evaluation systems and individual effort, proxied by the commonly used concept of work engagement. Using four waves of a new representative, linked employer-employee data set, the Linked Personnel Panel (LPP), we apply fixed effects estimations to account for unobserved heterogeneity. Our results show positive and statistically significant relationships between the presence of a performance management and evaluation process and employee engagement on the individual level. We are further able to differentiate between appraisal interviews and written target agreements which allows us to show a positive effect of appraisal interviews and an additional positive effect of target agreements. In addition, we find first evidence that these direct relationships are partially mediated by goal clarity and procedural fairness.
urn:nbn:de:bsz:21-dspace-1014701
Keywords: D23; J01; J33; M41; M52; 330; Target Agreements; Performance Appraisals; Work Engagement; Goal Clarity; Procedural Fairness